Hyponatraemia – the contribution of homeopathic product - Santos, Alexandra (2003)
The A.A. report the case of a 71-year-old female with severe hyponatraemia (101mmol/l),whose first clinical presentation was of convulsions and coma. This occurred after three daysof vomiting and exclusive tea ingestion.While taking the patient’s history, it emerged that several diuretic and natriuretic homeopathic products had been consumed. This, together with a poor sodium diet, is thought to have been largely responsible for the aetiopathogenesis of the clinical case reported.With the publication of this case, the authorswould like to underline the potential risks involved in the consumption of homeopathic products and consequently the importance of knowing their effects, as these products can cause serious illness.